Penerapan Nilai-Nilai Pendidikan Islam pada Santri dalam Program Pekan Dakwah Pondok Pesantren Modern Zam-Zam - Mulyadi; Makhful; Darodjat (Jurnal Dakwah dan Komunikasi, 2024)
This research describes: first, the implementation of the annual Ramadhan preaching week activities for students; second, application of Islamic educational values ​​in the da'wah week program; third, the internalization method in applying Islamic educational values ​​to the da'wah week program. This research method is qualitative field research. Data collection methods are observation, interviews and documentation. The results of this research indicate that the da'wah week program is an Islamic boarding school program that must be followed by class XI female students at the Zam Zam Cilongok modern Islamic boarding school. This da'wah week program is held in the first two weeks of the month of Ramadan. This program is running well and the implementation of Islamic values ​​is also implemented by students in their preaching environment.